Unclear Intentions: Eavesdropping in Microbial and Plant Systems - Rebolleda-Gómez, María; Wood, Corlett Wolfe (Frontiers in Ecology and Evolution, 2019)
Eavesdropping, the interception of signals by unintended receivers, is an important component of the ecology and evolution of communication systems. Plants and microbes have complex communication systems with important consequences for agriculture, human health and ecosystem functioning. Eavesdropping, however, has mostly been studied in animal systems. In this review, we argue that eavesdropping is an important force shaping the ecology and evolution of communication in these non-animal systems. To date, studying eavesdropping in plants and microbes has been limited by the fact that signaler “intention” is often unclear: distinguishing signals that evolved to convey information from unintended cues is particularly difficult in plants and microbes, and the fitness consequences of signalling are rarely measured. We describe some of the main examples of eavesdropping in plant and microbial communication and point out other murkier cases were the molecular and physiological basis of communication are well understood, but the evolutionary implications have not been addressed. We argue that these systems provide experimental tractability to test some of the predicted ecological and evolutionary consequences of eavesdropping, and that, the particularities of these systems can lead to an increased understanding of eavesdropping, and its importance in biological communication.